2008
DOI: 10.1111/j.1365-2036.2008.03783.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical trial: protective effect of a commercial fish protein hydrolysate against indomethacin (NSAID)‐induced small intestinal injury

Abstract: SUMMARY BackgroundA partially hydrolysed and dried product of pacific whiting fish is marketed as a health food supplement supporting 'intestinal health'.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 18 publications
1
35
0
1
Order By: Relevance
“…When cultured rat epithelia and human colon cells were given the Seacure â , cell growth was significantly increased (at 1 mg/ml concentration, p < 0.01) and the cell injury was significantly reduced (at 25 mg/ml concentration, p < 0.05) due to the action of ethanol-soluble di-and tri-peptides containing glutamine (Fitzgerald et al, 2005). A pilot human clinical trial using Seacure â pointed out that it could reduce the degree of small intestinal damage caused by the non-steroidal anti-inflammatory drug, indomethacin (Marchbank, Limdi, Mahmood, Elia, & Playford, 2008). This study also suggested that glutamine present in FPH might have contributed to antioxidative activity via stimulation of glutathione production.…”
Section: Functional Foods and Nutraceuticalsmentioning
confidence: 93%
“…When cultured rat epithelia and human colon cells were given the Seacure â , cell growth was significantly increased (at 1 mg/ml concentration, p < 0.01) and the cell injury was significantly reduced (at 25 mg/ml concentration, p < 0.05) due to the action of ethanol-soluble di-and tri-peptides containing glutamine (Fitzgerald et al, 2005). A pilot human clinical trial using Seacure â pointed out that it could reduce the degree of small intestinal damage caused by the non-steroidal anti-inflammatory drug, indomethacin (Marchbank, Limdi, Mahmood, Elia, & Playford, 2008). This study also suggested that glutamine present in FPH might have contributed to antioxidative activity via stimulation of glutathione production.…”
Section: Functional Foods and Nutraceuticalsmentioning
confidence: 93%
“…The antioxidative properties exhibited by meat/fish protein hydrolysates are mainly due to the several endogenous antioxidants present in skeletal muscle (Table 1). Fish protein hydrolysate is known not only to elevate plasma bile acids, reduce visceral adipose tissue mass in rats (Liaset et al 2009) but also reported to truncate the increased intestinal permeability in humans (Marchbank et al 2008). It is also reportedly known to reduce the symptoms of occasional diarrhoea and constipation, and alleviated bloating (Englender 2000).…”
Section: Meat Incorporated Foodmentioning
confidence: 99%
“…This product has been shown to reduce the degree of small intestine damage caused by non-steroid anti-inflammatory drugs in a cell model system and during a pilot human study (Fitzgerald et al, 2005;Marchbank, Limdi, Mahmood, Elia, & Playford, 2008).…”
mentioning
confidence: 97%